RANCANG BANGUN SISTEM INFORMASI PRESENSI MAHASISWA BERBASIS QR CODE DENGAN INTEGRASI NOTIFIKASI REAL-TIME BERBASIS WEB - Ridoh, Ahmad; Irdes Putra, Yogi; Yanti, Fitri; Pitra, Dedek Helida; Selpiani, Nevi (Information Technology Education Department, 2026)
The main problem in lecture management is the efficiency and accuracy of student attendance recording. Manual methods using paper-based signatures are still prone to fraud (attendance entrustment) and require a relatively long recapitulation process. This study aims to design a QR Code-based student attendance information system with real-time notifications to improve data integrity and administrative efficiency in academic processes. The system development method used is the Waterfall model, which consists of requirements analysis, design, implementation, testing, and maintenance stages. The study was conducted at the Information Technology Education Study Program, Universitas Muhammadiyah Muara Bungo, involving 20 students as research subjects. System testing was carried out through real classroom usage scenarios. The results show a QR Code scanning success rate of 90%, with 18 successful scans out of 20 trials. The average system response time is 1.1 seconds per transaction. The real-time notification feature achieved a 100% success rate without any failures in delivering notifications to both admin and lecturer dashboards. In addition, the system achieved 100% data accuracy with no duplication or missing records. The implementation of this system significantly improves attendance processing efficiency and reduces administrative time compared to manual methods. The analysis also indicates that lighting conditions and camera quality are key factors affecting QR Code scanning success. This system provides an effective solution for digitizing attendance management in higher education institutions. Keywords: Information Systems; Attendance; QR Code; Real-Time Notification; Waterfall.